LncRNA GHET1 has effects in development of pre‐eclampsia. Issue 8 (12th March 2019) - Li, Shuhong; Liu, Jie; Kong, Fanqiang; Wang, Yuanli; Li, Ning; Zou, Yanfen
Abstract: To explain long noncoding RNA (lncRNA) gastric carcinoma high expressed transcript 1 (GHET1) affects the mechanism in development of pre‐eclampsia. The pathological changes of normal, mild, and severe pre‐eclampsia were evaluated by hematoxylin and eosin staining and measured the lncRNA GHET1 expression in different tissues by reverse‐transcription polymerase chain reaction. In the cell experiment, the BeWo cells were randomly divided into three groups: normal control (NC) group, model group, and lncRNA group. The JEG3 cells of the model and lncRNA groups were cultured in the hypoxia condition. The JEG3 cells invasion and migration abilities were measured by Tanswell and wound‐healing assays. The relative protein expressions of different groups were evaluated by Western blot (WB) assay. Compared with normal puerperal, the lncRNA GHET1 gene expression of pre‐eclampsia was significantly downregulated ( P  < 0.05, respectively). In the cell experiment, the invasion cell number and wound‐healing rate of the model group were significantly suppressed compared with the NC group ( P  < 0.05, respectively). However, the invasion cell number and wound‐healing rate of lncRNA group were enhanced by lncRNA GHET1 overexpression ( P  < 0.05, respectively). In WB assay, the E‐cadherin, fibronectin, and vimentin proteins expression showed significant differences between the model and lncRNA groups ( P  < 0.05, respectively). lncRNA GHET1 overexpression had restored cell invasion and migration abilities reduced by hypoxia in pre‐eclampsia. Abstract : The histopathology and long noncoding RNA (lncRNA) gastric carcinoma highly expressed transcript 1 (GHET1) gene expression. A, the histopathology of normal placental tissue by hematoxylin and eosin (H&E) staining (×200); B, the histopathology of mild pre‐eclampsia (PE) placental tissue by H&E staining (×200); C, the histopathology of severe PE placental tissue by H&E staining (×200); D, the GHET1 gene expression of difference groups. * P  < 0.05 vs normal placental tissues; # P  < 0.05 vs mild PE placental tissues.